2008
DOI: 10.1029/2008gl035972
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric density in the Earth's magnetic cusp as observed by the Streak mission

Abstract: [1] Measurements of neutral gas density in the thermosphere at the base of the Earth's south magnetic cusp from the Streak mission are reported and discussed. In contrast to recent reports of enhanced density in the cusp, these measurements show the density to be depleted relative to the surrounding region. The difference is interpreted as an altitude effect. This observation and interpretation lead to new constraints on the physical mechanisms that could explain cusp upwelling and are inconsistent with a Joul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 14 publications
2
74
2
Order By: Relevance
“…The quantitative analysis for all three events presented in Table 1 indicate that stronger soft electron precipitation is accompanied by stronger density enhancements in the thermosphere, which further strengthens the importance of soft electron precipitation in thermospheric upwellings. Further arguments that support this can be found in Clemmons et al (2008) and Sadler et al (2012). Clemmons et al (2008) has explained density enhancements as a result of direct energy transfer from soft electrons to neutrals.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…The quantitative analysis for all three events presented in Table 1 indicate that stronger soft electron precipitation is accompanied by stronger density enhancements in the thermosphere, which further strengthens the importance of soft electron precipitation in thermospheric upwellings. Further arguments that support this can be found in Clemmons et al (2008) and Sadler et al (2012). Clemmons et al (2008) has explained density enhancements as a result of direct energy transfer from soft electrons to neutrals.…”
Section: Discussionmentioning
confidence: 65%
“…Further arguments that support this can be found in Clemmons et al (2008) and Sadler et al (2012). Clemmons et al (2008) has explained density enhancements as a result of direct energy transfer from soft electrons to neutrals. On the other hand, Sadler et al (2012) suggested that density enhancements could be explained as a combination of soft electrons which heat electrons in the thermosphere, and cause ion outflow.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…During the last decade, the variations, dynamical features, temperature and density structures in the polar cap and/or cusp region of the thermosphere/ionosphere have been clarified from radar and satellite observations (e.g., Innis and Conde, 2001;Maeda et al, 2002;Lühr et al, 2004;Liu et al, 2005;Fujiwara et al, 2007;Clemmons et al, 2008;Maeda et al, 2009, and references therein). In addition to recent works, Moe and Moe (2008) have reviewed historical studies on the high-latitude thermospheric mass density anomaly.…”
Section: Introductionmentioning
confidence: 99%